2016
DOI: 10.3892/ol.2016.4276
|View full text |Cite
|
Sign up to set email alerts
|

Nedaplatin sensitization of cisplatin-resistant human non-small cell lung cancer cells

Abstract: Abstract. Cisplatin (DDP) has been one of the most widely used chemotherapy drugs for advanced non-small cell lung cancer. However, the increase in the number of DDP-resistant cancer cells has become a major impediment in the clinical management of cancer. In the present study, for the first time, the 3-(4,5-dimethylthiazol-2yl)-2,5-diphenyltetrazolium bromide assay was used to demonstrate that nedaplatin (NDP) could have a stronger inhibitory effect than DDP alone in DDP-resistant A549 (A549DDP) cells and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Inhibition of these cyclins and CDKs results in the accumulation of cells in the S-phase (41). Other researchers have shown that cisplatin can arrest the cell cycle of A549 cells in the S-phase (30,42) or in G 2 /M phase (34). Cell-cycle arrest is a possible mechanism for growth inhibition and induction of apoptosis in A549 cells by platinum complexes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Inhibition of these cyclins and CDKs results in the accumulation of cells in the S-phase (41). Other researchers have shown that cisplatin can arrest the cell cycle of A549 cells in the S-phase (30,42) or in G 2 /M phase (34). Cell-cycle arrest is a possible mechanism for growth inhibition and induction of apoptosis in A549 cells by platinum complexes.…”
Section: Discussionmentioning
confidence: 94%
“…The ability of cisplatin to induce apoptotic cell death has already been reported not only for lung cancer cells (30) but also in other tumour cell lines of prostate (31), gastric (32) and bladder (33) cancer. Moreover, other newly synthesized platinum-based drugs induced apoptosis of different cell lines (14,(34)(35). Cisplatin and other platinum-based drugs induce apoptosis through several different mechanisms including activation of pro-apoptotic genes such as p53 upregulated modulator of apoptosis (PUMA) (36), caspases (37), P53-induced protein with a death domain (PIDD) (38), mitogen-activated protein kinase (MAPK) family (39), as well as through interaction with BCL2 family proteins in mitochondria or the cytosol (40).…”
Section: Discussionmentioning
confidence: 99%
“…A549 is a non-small cell lung cancer (NSCLC) cell line, the main cancer type nedaplatin is used for treating. A large number of publications have studied the antiproliferative effect of nedaplatin in NSCLC, with a few studies investigating the expression of apoptotic markers and altered cell cycle distribution in response to nedaplatin treatment [ 20 , 26 , 27 , 28 ]. However, genotoxicity or DNA damage induction, assumed to be the main mechanism of action of all platinum drugs, are not assessed in any of these publications and will be addressed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…It was approved in Japan for use in several cancers, including SCLC [46]. It has been allowed to be used in the treatment of esophageal cancer, lung cancer, gynecological cancer, head and neck tumors in China based on the results of many clinical trials, which showed that nedaplatin has similar anti-tumor therapeutic effects with a lower toxicity than cisplatin [47][48][49][50]. The common adverse effects of nedaplatin include bone marrow suppression, gastrointestinal symptoms, kidney dysfunction, ototoxicity, and alopecia, while allergic reaction and Adams-Stokes syndrome are rare complications [51].…”
Section: Discussionmentioning
confidence: 99%